Cypripedium subtropicum (Orchidaceae) employs aphid colony mimicry to attract hoverfly (Syrphidae) pollinators - Jiang, Hong; Kong, Ji-Jun; Chen, Hsin-Chun; Xiang, Zhen-Yong; Zhang, Wei-Ping; Han, Zhou-Dong; Liao, Pei-Chun; Lee, Yung-I (The New phytologist, 2020)
• In Orchidaceae, pollination is mostly animal-mediated, and one-third of species have evolved a deceptive pollination mechanism without rewards. Cypripedium is a representative lineage of nonrewarding orchids restricted to temperate regions. Cypripedium subtropicum flowers are pollinated by hoverflies and have hairy tufts that visually resemble an aphid colony covered with honey dew. • We recorded the behavior of hoverflies on the flowers, determined the breeding system of the species and the structure of hairy tufts, and investigated the roles of hairy tufts and floral volatiles in this specialized pollination by using pollination experiments, scanning electron microscopy, bioassays and chemical analyses. • The white hairy tufts covering the sidelobes of the labellum provide edible rewards and serve as crucial visual lures for hoverflies. The flowers emit primarily (E)-β-farnesene and a smaller amount of β-pinene that were found to attract hoverflies. • Our results suggest that C. subtropicum uses both visual mimicry of an aphid-colonized labellum with a reward and chemical mimicry of aphid alarm pheromones to attract hoverflies for pollination. This is the first described example of a rewarding mimicry system in plants, where the models are animals with their secretions and the reward is similar in nutrients to that of the model mimicked.